An assessment of theoretical knowledge and psychomotor skills of Basic Life Support Cardio-Pulmonary Resuscitation provision by Emergency Medical Services in a province in South Africa - Veronese, Jean-Paul Tyrone (Division of Emergency Medicine, 2016)
Includes bibliographical references